Single versus sequential culture medium: which is better at improving ongoing pregnancy rates? A systematic review and meta-analysis - Dieamant, Felipe; Petersen, Claudia G.; Mauri, Ana L.; Comar, Vanessa; Mattila, Marina; Vagnini, Laura D.; Renzi, Adriana; Petersen, Bruna; Ricci, Juliana; Oliveira, João Batista A.; Baruffi, Ricardo L.R.; Franco Júnior, Jose G. (JBRA assisted reproduction, 2017)
This study aimed to evaluate if single medium is better than sequential medium at improving ongoing pregnancy rates in patients undergoing assisted reproductive technology (ART) procedures. The data featured in this meta-analysis were extracted from four randomized controlled trials yielded from a systematic search carried out on electronic databases. The primary endpoint was ongoing pregnancy rate. Secondary endpoints included clinical pregnancy and miscarriage rates. The endpoints for ongoing pregnancy rate were also analyzed based on the time at which the embryo transfers were performed: cleavage stage (day 2/3) and/or blastocyst stage (day 5/6). There were no significant differences between single and sequential medium for clinical pregnancy (RR=1.09; 95%CI=0.83-1.44; p=0.53), ongoing pregnancy (RR=1.11; 95%CI=0.87-1.40; p=0.39), or miscarriage rates (RR=0.89; 95%CI=0.44-1.81; p=0.74). No significant difference was found for ongoing pregnancy rate (RR=1.29; 95%CI=0.93-1.78; p=0.12) between single and sequential medium when only trials in which embryos were transferred at the blastocyst stage were included. In conclusion, the choice of embryo culture approach - single or sequential medium - did not affect the ongoing pregnancy rates of patients undergoing ART cycles.